Cultural tourism and socio-economic regeneration of rural communities: the Apo festival of Bono Takyiman, Ghana. Issue 1 (2nd January 2023) - Quan-Baffour, Kofi Poku
ABSTRACT: Tourism has been part of humankind since time immemorial. People visit destinations for educational, religious, medical or entertainment purposes. Tourism includes short-term travel of people to destinations outside their communities. It is an important income generation and source of employment in many countries. In many former European colonies, some historical sites and events still attract thousands of visitors who like to get the first-hand information about the past. An important event that attracts thousands of visitors to rural Ghana is cultural tourism. It takes place when people visit specific destinations to attend, observe, learn or enjoy cultural events of an ethnic group. Ghana is endowed with a variety of festivals which attract local and foreign visitors. This study investigated the socio-economic impact of the annual Apo festival of Bono Takyiman. This qualitative-ethnographic research employed interviews and participant observation in the investigation. The study found that the Apo festival as a cultural tourism has a positive impact on the socio-economic development of the Bono Takyiman Municipality. In view of its positive impact on communities, the paper recommended to the local authorities to make the product more attractive for cultural tourism to contribute to the socio-economic regeneration of the countryside.